Assessing the leanness of government-linked companies and its influence on performance - Razalli, Mohd Rizal; Ahmad, Hartini; Mahmood, Rosli; Ahmad Arshad, Darwina; Abu Bakar, Lily Julienti (2012)
Leaning the operations processes in an organization has become one of the organizational goals. The expected benefits of lean would not only affect the internal process within organization but also go external to the customers.The government-linked companies are well-known for their big-sized establishment.Thus, the operational issues in GLCs are huge.It is interesting to investigate the leanness of Malaysian GLCs. At present,there is little known concerning the extent of lean implementation in the GLCs and the influence of such lean practices to their organizational performance.Hence, this paper would examine the leanness of GLCs in Malaysia In so doing, a total of 281 managers in GLCs were surveyed.The findings showed that the level of leanness was relatively high among the GLCs,while the lean management practice was significantly related to organizational performance.